Síndrome de hipotensão espontânea do líquor. - Rita Sousa; Raquel Gouveia; Leonor Lopes; Nuno Ruivo; Nuno Henriques; Graça Sá; David Coutinho; Jorge Campos (Acta Médica Portuguesa, 2003)
Spontaneous Intracranial Hypotension is a rare syndrome, characterized by orthostatic headaches, low CSF pressure and characteristic aspects on MRI. The authors describe a clinical case of Spontaneous Intracranial Hypotension, in which the MRI investigation revealed a low position of the cerebellar tonsils, a diffuse and symmetric dural enhancement and an engorgement of the cervical epidural venous plexus. The authors make a review of the physiopathology, clinical and radiological aspects related to this syndrome.